2013
DOI: 10.1007/s11906-013-0410-z
|View full text |Cite
|
Sign up to set email alerts
|

The Glycemic Effects of Antihypertensive Medications

Abstract: Older antihypertensive medications are believed to be associated with metabolic disturbances, especially raised glucose levels. Owing to this, many physicians shun their use. Newer antihypertensive medications are metabolically neutral or metabolically favorable; therefore, they are looked upon favorably and are chosen as primary medications for the treatment of hypertension. Here we review the literature on the glucose effects of older and newer antihypertensive medications. We also consider what, if any, imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Thus, with 24 hours since the last dose and with a half-life of 3 hours, the concentration during the OGTT was minimal. In addition, previous human studies have shown that β-blocking agents have either no effect or a slightly increasing effect on blood glucose, 7,43,44 contrasting to the decreased glucose levels observed in the patients with LQT2, thus ruling out that the lower glucose levels among LQT2 in comparison with control participants could be attributable to β-blocking agents. Actually, prior use may even have positive effects on recovery from hypoglycemia, 12 and a recent study of diabetic patients showed that prior use of β-blockers led to lower incidence of severe hypertension and hypokalemia during hypoglycemia and recommended incorporation of β-blockers for diabetes mellitus to reduce dangers associated with severe hypoglycemia.…”
Section: Discussionmentioning
confidence: 88%
“…Thus, with 24 hours since the last dose and with a half-life of 3 hours, the concentration during the OGTT was minimal. In addition, previous human studies have shown that β-blocking agents have either no effect or a slightly increasing effect on blood glucose, 7,43,44 contrasting to the decreased glucose levels observed in the patients with LQT2, thus ruling out that the lower glucose levels among LQT2 in comparison with control participants could be attributable to β-blocking agents. Actually, prior use may even have positive effects on recovery from hypoglycemia, 12 and a recent study of diabetic patients showed that prior use of β-blockers led to lower incidence of severe hypertension and hypokalemia during hypoglycemia and recommended incorporation of β-blockers for diabetes mellitus to reduce dangers associated with severe hypoglycemia.…”
Section: Discussionmentioning
confidence: 88%
“…However, caution should be taken when extrapolating results from nocturnal animals to humans, given the difference in diurnal pattern. Second, although our understanding of atenolol‐related glucose dysregulation is not yet complete, potential mechanisms for β‐blocker‐related hyperglycemia, including reduced insulin‐stimulated glucose uptake due to vasoconstriction, impairment of insulin release, weight gain, and increased hepatic glucose output have been proposed . It is possible that the observed aMT6s change might not play a major part in affecting glucose metabolism relative to other mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…First, the sample evaluated is quite heterogeneous and the doses of HC were significantly lower than those used in other studies. Second, few patients (13 out of 42) were treated with anti-hypertensive agents, calcium channel blockers and ARBs which could partly affect glucose metabolism 32 . Lastly, we did not assay circulating catecholamine levels which play a significant role in blood glucose regulation.…”
Section: Discussionmentioning
confidence: 99%